Pakistan's Agriculture in the 21st Century (The Pakistan Development Review, 1998)
In Pakistan, agriculture, which accounts for more than 20 percent of GDP and provides more than 50 percent of jobs, has a special role to play in growth, poverty reduction, and environmental protectiOl'. Agricultural growth in the past thirty years has been impressive, at more than 3 percent a year. Sources of growth, however, have changed over the years-from the seed, fertiliser, and irrigation package of the 1960s, to intensification of water and fertiliser use in the 1970s, to improvements in crop management and incentives in the 1980s. Those sources of growth have all but run their course, and agriculture growth in the next century will depend on increasing productivity. At present there are clear signs of stagnation in productivity growth. In fact, total factor productivity, a good measure of overall productivity, may even have declined since the mid-1970s due to resource degradation, failure to adapt technical change, and poor incentives, among others causes. Future growth through productivity increase, however, will require major changes in systems, policies, and institutions for agriculture. These changes are crucial because agriculture in the next century will continue to be key in achieving growth with poverty alleviation and environmental protection.